Négritude en question : de la valorisation de la culture noire à la contestation du mouvement - Kalinowska, Ewa (Romanica Silesiana)
The aim of the present article is to address the notion of négritude in its variety of aspects, as expressed in poetry, essays and novels. The movement founded its principles on the belief in a common black identity and was aimed at the elevation of the traditional African culture and heritage. Despite its undeniable positive influence, the movement met with criticism from a number of black intellectuals and writers who tended to regard it as being insufficiently militant and who pointed out that its concepts were based excessively on the “white aesthetic” and “the white man’s vision of the world”. Key words: Négritude, black culture, African traditions, glorification, negation.